"SCADA-BT - Detailed Technical Specification of SCADA-BT Modules - v1.3", Projeto SCADA-BT - QREN nº 24661 - Jorge Pereira (2015)
This document presents the detailed technical specifications for the main functionalities proposed for the LV SCADA system to be developed within the SCADA-BT project.Having as a basis the reference architecture and functional specification document previously issued, the technical details of the algorithms and execution procedures are here documented. The development of these technical specifications will enable the establishment of the necessary conditions for the industrial development and implementation process of a solution prototype.The modules that implement the main functionalities to be included in the LV SCADA are detailed, namely: Data Acquisition and Information Processing Module; Active Management of Generation and Load Module; Fault Management Module; Intelligent Management of Alarms Module; Interface to Corporative ICT Systems.A complete identification of data structures, APIs, inputs and outputs is provided in order to support the development of the proposed modules.